Out of the Cube: Augmented Rubik's Cube - Oriel Bergig; Eyal Soreq; Nate Hagbi; Kirill Pevzner; Nati Levi; Shoham Blau; Yulia Smelansky; Jihad El-Sana (International Journal of Computer Games Technology)
Computer gaming habits have a tendency to evolve with technology, the best being ones that immerse both our imagination and intellect. Here, we describe a new game platform, an Augmented Reality Rubik's cube. The cube acts simultaneously as both the controller and the game board. Gameplay is controlled by the cube, and game assets are rendered on top of it. Shuffling and tilting operations on the cube are mapped to game interaction. We discuss the game design decisions involved in developing a game for this platform, as well as the technological challenges in implementing it. Ultimately, we describe two games and discuss the conclusions of an informal user study based on those games.